Sistem Monitoring dan Kontrol Tanaman Tin Berbasis IoT - Farhan Hazim; Cyntia Widiasari (Politeknik Caltex Riau, 2021)
Tin plants have various health benefits and high economic value, but these plants need attention in order to develop properly, so an IoT-based fig plant monitoring and control system is created. The system can find out the temperature, soil moisture, soil pH, and fruit color through sensors installed and forwarded to the owner's smartphone for monitoring the plants through the Blynk application, and can water automatically when the soil starts to dry and notify when the fruit is ripe. The system is also equipped with backup energy from a 6watt solar cell which from the test results is able to run the system with a load of +/- 17 hours. Solar cells are used if there is a disturbance in the main energy. The components needed in building this system are a microcontroller, sensors, relays, water pumps, solar cells, and batteries. The test results of the DS18B20 temperature sensor have an accuracy of 98.99%, the humidity sensor has an accuracy of 86.94% and the soil pH sensor has an accuracy of 98.22%. With this system, information on the condition of tin plants can be found through the Blynk application. The hope is that this tool can help plant owners to monitor their plants and can optimize plant growth with good care.